FleQ, FleN and c-di-GMP coordinately regulate cellulose production in Pseudomonas syringae pv. tomato DC3000 - Martínez-Rodríguez, Laura; López-Sánchez, Aroa; García-Alcaide, Andrea; Govantes, Fernando; Gallegos, María-Trinidad (Frontiers in Molecular Biosciences, 2023)
The second messenger cyclic di-GMP (c-di-GMP) controls the transition between motility and sessility in many bacterial species by a variety of mechanisms, including the production of multiple exopolysaccharides. Pseudomonas syringae pv. tomato (Pto) DC3000 is a plant pathogenic bacteria able to synthesize acetylated cellulose under high c-di-GMP levels thanks to the expression of the wssABCDEFGHI operon. Increased cellulose production enhances air-liquid biofilm formation and generates a wrinkled colony phenotype on solid media. We previously showed that under low levels of c-di-GMP, the regulators FleQ and AmrZ bound to adjacent sequences at the wss promoter inhibiting its expression, but only FleQ responded to the presence of c-di-GMP by activating cellulose production. In the present work, we advance in the knowledge of this complex regulation in Pto DC3000 by shedding light over the role of FleN in this process. The distinctive features of this system are that FleN and FleQ are both required for repression and activation of the wss operon under low and high c-di-GMP levels, respectively. We have also identified three putative FleQ binding sites at the wss promoter and show that FleQ/FleN-ATP binds at those sites under low c-di-GMP levels, inducing a distortion of DNA, impairing RNA polymerase binding, and repressing wss transcription. However, binding of c-di-GMP induces a conformational change in the FleQ/FleN-ATP complex, which relieves the DNA distortion, allows promoter access to the RNA polymerase, and leads to activation of wss transcription. On the other hand, AmrZ is always bound at the wss promoter limiting its expression independently of FleQ, FleN and c-di-GMP levels.